APPLICATION OF ICT BASED CONTEXTUAL APPROACH TO IMPROVE WRITING SHORT STORY SKILL AND LEARNING INTEREST OF SENIOR HIGH SCHOOL STUDENTS - Evi Susanti; Juarni Juarni; Teti Sobari (JLER (Journal of Language Education Research), 2018)
The research is a quasi- experintal research which background is the low motivation of short-story writing eleventh grader high school students. The purpose of this research is to review students short-story  writing  ability using ICT-based contextual approach and normal approach. The random sample choice in this research in the students of eleventh grader of SMA Padalarang students with 30 sample students for experiment class and 28 students sample for control class. Based on data sample processing using SPSS 22 for windows from result of data processing obtained the significance value is 0,02 because the significance value >0,05 then is rejected, result show that the learning using ICT-based contextual  approach is better than normal leaning.